The Benefit of Tandem Application in Enhancing English Speaking Skills - Shofa, Faisa Laili; Hariyanti, Annisa Dila; Rizqiyah, Risma; Lyaningtyas, Lyaningtyas; Ma’rufah, Desi Wijayanti (Proceedings Series on Social Sciences & Humanities, 2025)
English is a global language that people used to interact with one another in all parts of their lives, including technology. The need for English was unavoidable. As the age progresses, many technologies are being developed to meet human needs. To meet this need, many English learning applications have been developed to help humans learn English only through applications. One example is the tandem application. Tandem learning, applying English learning basics that are easy to understand. This study tries to understand how tandem applications can improve the speaking ability of English learners. This study uses a qualitative approach with a qualitative descriptive study method as the research method. Qualitative research method is research that describes social influences that cannot be explained, measured, or described through a quantitative approach. While descriptive qualitative research is a research strategy in which the researcher investigates events, phenomena in the lives of individuals and asks a person or group of individuals to tell their lives. easy to-understand explanations. In conclusion, the Tandem application proves to be a powerful tool for improving English-speaking skills, combining linguistic practice with cultural exchange. While challenges remain, its potential for facilitating meaningful and practical language learning experiences is undeniable.